2000
DOI: 10.1161/01.cir.102.7.813
|View full text |Cite
|
Sign up to set email alerts
|

Transcatheter Implantation of a Bovine Valve in Pulmonary Position

Abstract: Background-Pulmonary regurgitation can lead to severe right ventricular dysfunction, which is a delicate postoperative problem in the long-term follow-up of patients who had surgery for congenital heart diseases. Clinical conditions of patients suffering from pulmonary valve incompetence are improved by valve replacement with a prosthetic valve. To date, the surgical approach is the only option to replace a pulmonary valve. We report the first experience of percutaneous pulmonary valve implantation. Methods an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
175
0
6

Year Published

2003
2003
2021
2021

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 291 publications
(185 citation statements)
references
References 12 publications
4
175
0
6
Order By: Relevance
“…An intriguing additional therapeutic option may exist in those patients in whom pulmonary regurgitation is predominantly from 1 pulmonary artery. Insertion of a valved stent 26 in the LPA might be expected to reduce total regurgitation by up to 100% in some patients and may be a particularly attractive option in those patients with a grossly dilated right ventricular outflow tract, who would otherwise be unsuitable for implantation of an existing valved stent in the MPA.…”
Section: Discussionmentioning
confidence: 99%
“…An intriguing additional therapeutic option may exist in those patients in whom pulmonary regurgitation is predominantly from 1 pulmonary artery. Insertion of a valved stent 26 in the LPA might be expected to reduce total regurgitation by up to 100% in some patients and may be a particularly attractive option in those patients with a grossly dilated right ventricular outflow tract, who would otherwise be unsuitable for implantation of an existing valved stent in the MPA.…”
Section: Discussionmentioning
confidence: 99%
“…While resolving the problem of conduit obstruction, bare stent placement leads to creation or exacerbation of pulmonary regurgitation. To overcome this problem, Bonhoeffer et al reported the first transcatheter pulmonary valve replacement (TPVR) in 2000 using a biological valve harvested from a bovine jugular vein (Medtronic, Minneapolis, MN) and sewn within a balloon-expandable Cheatham Platinum Stent (NuMED, Hopkinton, NY) [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…Four of the valves were mobile and competent with slight stenosis secondary to visible calcification in the fifth one. Although the overall success rate was low at about 36%, these attempts provided the platform for human studies [11].…”
Section: Historymentioning
confidence: 99%